PERANAN AUDIT INTERNAL DALAM MANAJEMEN RISIKO BANK - ARWINA KARMUDIANDRI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of risk management is the availability of policies, procedures and risk management methodologies so that bank operations can still be controlled at an acceptable limit and give the advantage to the Bank. Application of risk management at the Bank has generally been going well. Contributions of internal audit in risk management, especially credit risk management is good enough, as evidenced by the achievement of significant reduction in NPLs. Internal audit has implemented a risk based audit in the implementation already running optimally and sustainably made and in collaboration with the Strategic Business Units in terms of risk management.